(3Mb GdeJge aj GdGSJYGfI HeMGe aj bGfhf GdELQGAGJ GdLfGFjI Gdjefj hGdeUQj (B: s (3OQGSI ebGQfI (B/ s - (3PcQi aVd YHOGddgs; (3YeQ eMeO SGde (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3Ef gPg GdQSGdI JJfGhd ehVhY Mb GdeJge ai GdESJYGfI HeMGe ai GdELQGAGJ GdLfGFjI(B: (3h gh ef GdehGVjY GdgGeI dJMbjb GdYOGdI ai eNJda eQGMd GdOYhi GdLfGFjI(B. (3h bO HOCJ gPg GdQSGdI HaUd JegjOi GSJYQVJ ajg GdJCUjd GdJGQjNi dMb GdeJge ai GdGSJYGfI HeMGme(B: (3Ke bSeJ GdOQGSI Edi KdGKI CHhGH JfGhdJ ajgG GdMb ai Cf jSJYjf HeMGe ai GdeQGMd GdeNJdaI ddOYhi GdLRGFjI(B: (3h Pdc ai eQMdI LeY GdGSJOdGdGJ h ai eQMdI GdJMbjb GdGHJOGFi eY YQV GdGJLGgGJ GdeNJdaI GdabgjI h GdbGfhfjI ShGA GdeDjOI Ch GdeYGQVg dgPG GdMb(B: (3ceG YQVJ Mb GdeJge ai Cf jSJYjf HeMGe ai eQMdI GdeMGceI GdLfGFjI HeNJda CfhGY GdeMGce ShGA GdYGOjI efgG Ch GdGSJKfGFjI(B: (3h JfGhdJ cPdc GdVeGfGJ GdgGeI GdJi jJeJY HgG GdeJge h GdeMGei ai CKfGA GSJNOGe gPG GdMb h cPdc GdLRGAGJ GdJi JJQJH Ydi YOe MeGjI gPG GdMb(B: (3h YQVJ CjVG Mbhb GdeMGei GdeNJdaI GdJi JfTC dg YfO eeGQSJg degfJg ai GdOaGY Yf GdeJge h cPdc GdMUGfI GdJi jJeJY HgGs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2017.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3Mb GdGSJYGfI HeMGes; (3GdVeGfGJ GdebQQI ddeMGes; (3GdMeGjI GdbGfhfjI dMb GdeJges; (3MeGjI GdeJge s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs